The Relationship Between Perforator Vein and Great Saphenous Vein Reflux with Leg Pigmentation in Patients with Chronic Venous Disease (Ceap C3 and C4) - Abdur Rahman; Dedy Pratama; Dewi S Soemarko (Green Publisher Indonesia, 2026)
Leg pigmentation is an important manifestation of chronic venous disease (CVD) due to long-term venous hypertension. Perforator vein and saphenous vein reflux are thought to play a major role in these skin changes. This prospective cross-sectional study involved 40 patients with CVD CEAP C3–C4 who underwent Doppler ultrasound examination at Cipto Mangunkusumo Hospital (RSCM) and Hermina Hospital in Depok between August and October 2025. Perforator vein and saphenous vein reflux were assessed using Doppler ultrasound, while pigmentation was assessed using the Venous Clinical Severity Score (VCSS). Bivariate and multivariate analyses were performed. Cockett perforator vein reflux was found in 17 patients (42.5%) and Boyd in 6 patients (15.0%). Saphenous vein reflux was found in almost all patients, with a distribution: SFJ 100%, mid-thigh 95.0%, lower thigh 82.5%, upper knee 70.0%, and lower knee 57.5%. Cockett and Boyd perforator reflux were significantly associated with the incidence of pigmentation (p < 0.05). In multivariate analysis, saphenous vein reflux in the upper knee segment was significantly associated with pigmentation (p = 0.020; aOR 10.24; 95% CI 1.445–72.57), as was prolonged standing (p = 0.032; aOR 6.54; 95% CI 1.17–36.52). Perforator vein reflux and saphenous vein reflux were significantly associated with the incidence of leg pigmentation in patients with chronic venous disease CEAP C3 and C4.